"Texting in their pockets": Millennials and rule violations in the hospitality industry. (December 2016) - Rosa, Nicole Baker; Hastings, Sally O.
Abstract: This article takes a communication perspective to examine rule violations among Millennial employees. Rule violations are treated as a focal concern because they provide insight into how organizations socialize Millennials into their culture and how Millennials make inroads toward transforming the organization. Twenty-five managers in the hospitality industry were interviewed to learn about their perceptions of Millennial employees. Three categories of organizational rules are examined: policies regarding cell phone use, policies regarding requesting time off, and civility. These themes are explored with respect to how normative and code rules coalesce in order promote assimilation and change. The findings also point to the implications that new generational cohorts have for collective assimilation and change for the organizational culture and the concomitant implications for managers.